2014
DOI: 10.1016/j.margeo.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tsunami hazard to the U.S. Atlantic margin

Abstract: Keywords: submarine landslides meteo-tsunami earthquakes and landslides probabilistic hazard assessment Tsunami hazard is a very low-probability, but potentially high-risk natural hazard, posing unique challenges to scientists and policy makers trying to mitigate its impacts. These challenges are illustrated in this assessment of tsunami hazard to the U.S. Atlantic margin. Seismic activity along the U.S. Atlantic margin in general is low, and confirmed paleo-tsunami deposits have not yet been found, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 156 publications
(232 reference statements)
0
52
0
Order By: Relevance
“…This method complements PTHA designed for geologic sources (ten Brink et al 2014) for a comprehensive assessment of long-wave coastal hazards. The demonstration study described in the previous section is a simple implementation of the probabilistic method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method complements PTHA designed for geologic sources (ten Brink et al 2014) for a comprehensive assessment of long-wave coastal hazards. The demonstration study described in the previous section is a simple implementation of the probabilistic method.…”
Section: Discussionmentioning
confidence: 99%
“…In PTHA, sources are commonly restricted in space to major fault zones (earthquakes) or continental/island margins (landslides) (ten Brink et al 2014) and the aggregation equations include a second integral over location. In contrast, the source parameter vector for meteotsunami hazards w i Ă° Þ includes a distributed location parameter (e.g., shoreline crossing coordinate), similar to what is specified in probabilistic storm surge analysis.…”
Section: Probabilistic Frameworkmentioning
confidence: 99%
“…The E/V Nautilus NA035 Expedition provided new insights into the geology and earthquake hazards as well as the distribution, abundance, and community structure of deep-sea benthic communities (ten Brink et al 2014 ). In the absence of dedicated digital cameras, frame grabs from the HD videos provided qualitative data from multiple angles and magnifi cations (Figs.…”
Section: Rov Video Surveysmentioning
confidence: 99%
“…Concerning the potential causal processes, as discussed in the above references, the triggering mechanism could have been a combination of low sea level, sediment oversupply, over-steeping of the shelf/slope, presence of gas and seismic activity. This paper is aimed to conduct an exploratory modelling study on the tsunamis that A statistical analysis for 160 landslide scars in the salt, fl uvial and glacial portions of the U.S. mid-Atlantic margin, with volumes ranging from 10 −3 up to 40 km 3 , has been published by ten Brink et al [21]. They found that landslide volume increases almost linearly with area, which allows to infer that most landslides on the margin must be translational, failing along depositional layer boundaries separating units of similar thickness, and having low shear strength.…”
Section: Introductionmentioning
confidence: 99%